2015
DOI: 10.1039/c5ra10021f
|View full text |Cite
|
Sign up to set email alerts
|

Promoted performance of a MnOx/PG catalyst for low-temperature SCR against SO2poisoning by addition of cerium oxide

Abstract: Manganese oxide supported palygorskite (MnO x /PG) catalysts are considered highly efficient for lowertemperature selective catalytic reduction (SCR) of flue gas NO by ammonia. However, during the SCR reaction, the surface of the MnO x /PG catalyst tends to get poisoned by SO 2 . In this study, we have doped the MnO x /PG catalyst with cerium oxide to improve their resistance against SO 2 poisoning. The SCR activity of the CeO 2 -doped catalyst (Mn-Ce/PG) is found to be remarkably higher than that of the undop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…enhancing the resistance to H 2 O and SO 2 , the composite-oxides, such as Mn confined titania nanotubes (Mn/TNT)[99], M-Mn/TiO 2 (M = Fe[100][101][102][103][104], Co[105][106][107], Ce[105,108], Ni[109], W[110] etc. ), Fe-Mn/Ti-Zr[111], MnO x /Fe-Ti[112], MnO x /CeO 2 -TiO 2[113], Mn-Ce/PG (palygorskite)[114], MnO x /Ce 0.8 M 0.2 O 2 (M = Ti, Sn) [115], MnO x(0.6) /Ce 0.5 Zr 0.5 O 2 , [116] MnO 2 /Ce (1−x) Zr x O 2 -TiO 2 , [117] MnO 2 -Ce (1−x) Zr x O 2 /TiO 2 [118], SO 4 2Ho 0.1 Mn 0.4 /TiO 2 catalyst presented a broad operating temperature window in the range of 60-200 • C and exhibited superior sulfur-poisoning resistance with 80% NO x conversion in the presence of 200 ppm SO 2 and 15% H 2 O at 120 • C. Shen et al [116] found that MnO x(0.6) /Ce 0.5 Zr 0.5 O 2 displayed a good resistance to 3% H 2 O and 100 ppm SO 2 that remained 90% NO conversion at 180 • C over the course of 5 h. Qiu et al [119] found that the SO 4 2− -Mn-Co-Ce/Ti-Si catalyst has an excellent SO 2 durability at low temperatures. However, these catalysts show a relatively good resistance for a short time.…”
mentioning
confidence: 99%
“…enhancing the resistance to H 2 O and SO 2 , the composite-oxides, such as Mn confined titania nanotubes (Mn/TNT)[99], M-Mn/TiO 2 (M = Fe[100][101][102][103][104], Co[105][106][107], Ce[105,108], Ni[109], W[110] etc. ), Fe-Mn/Ti-Zr[111], MnO x /Fe-Ti[112], MnO x /CeO 2 -TiO 2[113], Mn-Ce/PG (palygorskite)[114], MnO x /Ce 0.8 M 0.2 O 2 (M = Ti, Sn) [115], MnO x(0.6) /Ce 0.5 Zr 0.5 O 2 , [116] MnO 2 /Ce (1−x) Zr x O 2 -TiO 2 , [117] MnO 2 -Ce (1−x) Zr x O 2 /TiO 2 [118], SO 4 2Ho 0.1 Mn 0.4 /TiO 2 catalyst presented a broad operating temperature window in the range of 60-200 • C and exhibited superior sulfur-poisoning resistance with 80% NO x conversion in the presence of 200 ppm SO 2 and 15% H 2 O at 120 • C. Shen et al [116] found that MnO x(0.6) /Ce 0.5 Zr 0.5 O 2 displayed a good resistance to 3% H 2 O and 100 ppm SO 2 that remained 90% NO conversion at 180 • C over the course of 5 h. Qiu et al [119] found that the SO 4 2− -Mn-Co-Ce/Ti-Si catalyst has an excellent SO 2 durability at low temperatures. However, these catalysts show a relatively good resistance for a short time.…”
mentioning
confidence: 99%
“…(2). the weight loss at 200-400 °C could be attributed to decomposition of ammonium salts [41][42][43].…”
Section: Scr Reactions With Somentioning
confidence: 99%
“…There are plenty of reviews for cerium-based catalysts. [43][44][45] Tang et al 43 explained the interaction between the active component and the reactants (NO, NH 3 and O 2 ) of ceriumbased catalysts in detail. Shan et al 44 comprehensively reviewed CeO 2 when used as a support, main active component, and promoter.…”
Section: Introductionmentioning
confidence: 99%